1,5-Dicyanoanthraquinone - Armaghan, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The complete molecule of the title compound, C(16)H(6)N(2)O(2), which is generated by a crystallographic inversion centre, is almost planar (r.m.s. deviation = 0.04 angstrom). In the crystal, adjacent molecules are stacked along the a axis, with a shortest centroid-centroid separation of 3.826 (2) angstrom.